Lina Bo Bardi reloaded: remains, memories, latencies - Bierrenbach, Ana Carolina de Souza; Rossetti, Eduardo Pierrotti (Risco - Journal of Architecture and Urbanism, 2014)
The article discusses the work of Lina Bo Bardi in Salvador, exploring the transformations that both works of architecture, such as urban design for the Historical Center suffered in the last 25 years. So between the design and the current situation of the framework of the city can regain the sense of celebrating the centenary of Lina Bo Bardi without incurring nostalgia, pointing to a critical investigation of the transformations for which the competing approaches to the management the city and its public spaces. Interested in promoting discussion to critically resume work and issues of Lina Bo Bardi without forgetting the processes of destroying his work.